2014
DOI: 10.1590/0103-9016-2013-0322
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability among sorghum accessions for seed starch and stalk total sugar content

Abstract: Sorghum (Sorghum bicolor (L.) Moench) is a staple food grain in many semi-arid and tropical areas of the world, notably in sub-Saharan Africa because of its adaptation to harsh environments. Among important biochemical components for sorghum for processors are the levels of starch (amylose and amylopectin) and total sugar contents. The aim of this study was to determine the genetic variation for total starch in the seed, its components and total sugar in the stalks of the sorghum accessions from Ethiopia and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
2
9
1
1
Order By: Relevance
“…The genotypic variability of 23 sorghum accessions is high, as indicated by the spread of samples across four quadrants in two-dimensional plot of PCoA (Figure 3). The spread of accessions across four quadrants in the scatterplot indicated high genetic variability (Gerrano et al 2014). PCoA is used as a complementary method to cluster analysis because this method is superior compared to other graphical dispersion analysis in terms of projection of distances representing the level of genetic diversity and identification of closely related genotype groups (Sant'Anna et al 2020).…”
Section: Genotypic Variability and Relationships Of S Bicolor Accessmentioning
confidence: 99%
“…The genotypic variability of 23 sorghum accessions is high, as indicated by the spread of samples across four quadrants in two-dimensional plot of PCoA (Figure 3). The spread of accessions across four quadrants in the scatterplot indicated high genetic variability (Gerrano et al 2014). PCoA is used as a complementary method to cluster analysis because this method is superior compared to other graphical dispersion analysis in terms of projection of distances representing the level of genetic diversity and identification of closely related genotype groups (Sant'Anna et al 2020).…”
Section: Genotypic Variability and Relationships Of S Bicolor Accessmentioning
confidence: 99%
“…Some genotypes recorded either lower or higher starch concentration due to high diversity of genotypes used in the present study. [14] reported starch concentration range of 60-75 g/100 g; [4] reported starch concentration range of 44.39% to 68.08% using 22 sorghum accessions mostly from Ethiopia and South Africa. However, it was suggested that starch concentration in sorghum is highly affected by genotype and environment [31].…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%
“…Sorghum have a wide genetic diversity in its physical structure and or chemical composition and therefore presenting benefits in hybridization [3]. Variation in structure, nutritional composition and phytochemical composition is critical for selection of desired traits in sorghum breeding [4]. The inheritable qualitative traits in sorghum kernel consist of pericarp color, pericarp thickness, presence of testa, testa color, and endosperm texture; while quantitative traits include grain size and weight [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of different molecular markers were applied in the whole genome analysis of sorghum up today. Five races of Sorghum bicolor were subjected to DArT markers analysis by MACE et al (2008), microsatellite markers represented by SSR and ISSR were reported for different sorghum accessions (EL HUSSEIN et al, 2014;TOO et al, 2018) and AFLP markers were applied by GERRANO et al (2014). RAPD markers were applied previously in the screening of population variability of 33 populations of the Moroccan landraces (MEDRAOUI et al, 2007); 37 accessions including released varieties, hybrids and their parental lines were analyzed by ARYA et al (2006), 32 accessions by JEYA et al (2006) and 40 accessions of sorghum with different technological use by SINHA et al (2014).…”
Section: Introductionmentioning
confidence: 99%